2004
DOI: 10.1191/1352458504ms1114oa
|View full text |Cite
|
Sign up to set email alerts
|

A randomized open label study of pain medications (naproxen, acetaminophen and ibuprofen) for controlling side effects during initiation of IFN β-1a therapy and during its ongoing use for relapsing-remitting multiple sclerosis

Abstract: Multiple sclerosis (MS) patients initiating IFN beta-1a, Avonex, therapy (Group 1, n = 30) or experiencing side effects after 6 months on therapy (Group 2, n = 30) were randomized for 5 weeks open label adjunct therapy to naproxen (Aleve), acetaminophen (Tylenol) or ibuprofen (Advil). Our hypothesis was that non-prescription pain medications are effective in decreasing or alleviating the side effects associated with IFN beta-1a therapy. Contrary to the hypothesis, most patients in both groups continued to repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…The panel reviewed three studies 25,27,28 that attempted to determine the most effective analgesic for FLS management. When the efficacies of acetaminophen, ibuprofen, and the steroid prednisone were compared, no significant difference was found between the treatment options in the first month of therapy with IM IFNβ-1a.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The panel reviewed three studies 25,27,28 that attempted to determine the most effective analgesic for FLS management. When the efficacies of acetaminophen, ibuprofen, and the steroid prednisone were compared, no significant difference was found between the treatment options in the first month of therapy with IM IFNβ-1a.…”
Section: Methodsmentioning
confidence: 99%
“…27 Similarly, Reess et al 25 compared acetaminophen and ibuprofen and found them equally effective at FLS management in patients initiating IM IFNβ-1a. Leuschen et al 28 compared the efficacy of naproxen, ibuprofen, and acetaminophen and found that the first two were more effective than the last at minimizing many of the physical symptoms associated with IM IFNβ-1a. However, none of these therapies was as effective as originally hypothesized of FLS at the 4-to 6-hour time point and at the 12-to 15-hour time point was significantly reduced with both 3-week titration (P < .001 at 4-6 hours; P = .006 at 12-15 hours) and 6-week titration (P = .023 at 4-6 hours; P = .027 at 12-15 hours).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Further testing of the effect of IFNβ treatment in the in vivo HD animal models using methods such as intraperitoneal injection 42 may serve as a proof of concept of potential NUB1-mediated therapy. Given the many side effects of IFNβ, [44][45][46] low-molecular-weight compounds that are easier to deliver or less toxic are more desired compared to IFNβ. Finding such compounds could be achieved by screening for transcriptional enhancers of NUB1 by minigene assays.…”
Section: Targeting Strategies For Nub1mentioning
confidence: 99%
“…To date, NSAIDs have been administered to patients to treat flu-like symptoms without taking into consideration of their potential role in oligodendrocytes survival and myelin protection (41)(42)(43)(44)(45)(46). Nevertheless, some NSAIDs were shown to ameliorate fatigue (approximate percentage of improvement: 10-20% with aspirin, 30% with naproxen, and 20% with ibuprofen) and improve cognitive abilities (approximate fold change of improvement: 1-fold with naproxen, 0.5-fold with ibuprofen, and 2-fold with acetaminophen) (46,47). It could be hypothesized that these effects may be secondary to the attenuation of brain pathology due to NSAIDs treatment, as suggested by the following data from experimental models of multiple sclerosis.…”
Section: Nsaids Treatment In Patients Affected By Multiple Sclerosismentioning
confidence: 99%